Analysis and assessment of landscape conditions on the territory of the Akmola region (Journal of Geography and Environmental Management, 2018)
The article substantiates the necessity of using a landscape approach for in-farm land management, analyzes the natural and climatic potential for the distribution of grain production. Based on the agroecological potential of specific agricultural enterprises in the Akmola region, zoning of territories was carried out on the basis of agro-ecological factors and a technique for agro-landscape microzoning and agro-landscape zoning was proposed. These methods can be used for intra-farm organization of territories.The given data will allow the land management bodies of the Akmola region to determine the scope of design works for on-farm land management on a landscape basis in each administrative area. The basis for the drafting of the organization of the territory of agricultural enterprises, taking into account the landscape conditions, is land zoning. In modern market conditions, diversification of crops plays a big role in the growth of economic development and stability of agricultural producers. With a view to furtherdevelopment of the agro-industrial sector, work is underway to further consolidate the agricultural formations and their specialization, which contributes to the activation of the process of introducing advanced technologies and the renewal of the machine and tractor fleet with high-performance machinery.